2012
DOI: 10.1590/s0100-204x2012000200005
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidade genética de Phakopsora pachyrhizi avaliada por meio de marcadores microssatélites

Abstract: Resumo -O objetivo deste trabalho foi avaliar a variabilidade genética da ferrugem-asiática-da-soja no Brasil, com uso de marcadores microssatélites. Populações de esporos de Phakopsora pachyrhizi coletadas nas regiões Sul, Sudeste e Centro Oeste do país foram submetidas à análise de variabilidade genética, avaliada por meio de marcadores microssatélites específicos para o fungo. Foram coletadas, também, populações de fungo em diversas variedades de soja em uma mesma localidade, incluindo populações com lesão … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
(24 reference statements)
0
3
0
1
Order By: Relevance
“…Pathogens and hosts coevolve allowed the emergence of different types of specialization to overcome the resistance of plants (Futuyma 2009). Therefore, the possibility of resistance breakdown increases as pathogen variability increases, especially for varieties that contain few vertical resistance genes (Tschurtschenthaler et al 2012). In this context, the addition of genes of diffreent origin to the genotypes identified as asymptomatic and potentially resistant to witches' broom in our study should be important to assure that new progenies are more resistant to new fungal strains.…”
Section: Discussionmentioning
confidence: 90%
“…Pathogens and hosts coevolve allowed the emergence of different types of specialization to overcome the resistance of plants (Futuyma 2009). Therefore, the possibility of resistance breakdown increases as pathogen variability increases, especially for varieties that contain few vertical resistance genes (Tschurtschenthaler et al 2012). In this context, the addition of genes of diffreent origin to the genotypes identified as asymptomatic and potentially resistant to witches' broom in our study should be important to assure that new progenies are more resistant to new fungal strains.…”
Section: Discussionmentioning
confidence: 90%
“…The weather conditions were similar for both fields during the soybean season, especially the monthly mean rainfall, which is generally the factor most contributing to rust severity, and studies of genetic variability showed a tendency to cluster samples of the southern region of Brazil (Tschurtschenthaler et al ., ) where both fields are located. Therefore, the reduced fitness of isolates from the conventional field may be related to the lower sensitivity to tebuconazole.…”
Section: Discussionmentioning
confidence: 99%
“…Obtaining cultivars resistant to all isolates of P. pachyrhizi is a complex process, due to the great genetic variability of the population (Sinclair & Hartman, ; Yamaoka et al ., ; Bonde et al ., ; Freire et al ., ; Tschurtschenthaler et al ., ), and so the use of fungicides is currently the main control measure.…”
Section: Introductionmentioning
confidence: 99%
“…pachyrhizi, devido à existência de tal variabilidade, a utilização de cultivares de soja com genes únicos de resistência vertical pode levar à rápida seleção de biótipos que quebrem a resistência dessas cultivares (TSCHURTSCHENTHALER et al, 2012).…”
Section: Resistência Genéticaunclassified